Gamification Implementation in Health Service Website in 5.0 Society Era - Ricky Muhammad Ramdhani; Aditya Dwi Nurrahman; Prayogi Haris Affendi; Leonardi Paris Hasugian; Agis Abhi Rafdhi (Universitas Komputer Indonesia, 2021)
The purpose of this research is to identify how to implement the gamification concept for health service in the 5.0 Society Era. This research is done in qualitative method with descriptive study approach. The results from this research are the increase in public awareness to maintaining their health with the application of gamification element on the health service website. Gamification in health service website interface means presenting game elements in user mechanisms to increase public participation in the needs of everyday health information. This research is to know how to implement the gamification concept in the public health service website in the 5.0 Society Era. The benefit of this research is to increase health public awareness from the gamification web interface and provide health information.